If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -4) + 52 = 6x + 4 Reorder the terms: 3(-4 + 4x) + 52 = 6x + 4 (-4 * 3 + 4x * 3) + 52 = 6x + 4 (-12 + 12x) + 52 = 6x + 4 Reorder the terms: -12 + 52 + 12x = 6x + 4 Combine like terms: -12 + 52 = 40 40 + 12x = 6x + 4 Reorder the terms: 40 + 12x = 4 + 6x Solving 40 + 12x = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 40 + 12x + -6x = 4 + 6x + -6x Combine like terms: 12x + -6x = 6x 40 + 6x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 40 + 6x = 4 + 0 40 + 6x = 4 Add '-40' to each side of the equation. 40 + -40 + 6x = 4 + -40 Combine like terms: 40 + -40 = 0 0 + 6x = 4 + -40 6x = 4 + -40 Combine like terms: 4 + -40 = -36 6x = -36 Divide each side by '6'. x = -6 Simplifying x = -6
| 5x+1=6x+17 | | 3x+52=80 | | 2015=101b+19a | | 3c-7=-3+1 | | 47=47-8(5-1w) | | 2y=3y+19 | | 4x-2=2x+x+4 | | 1v+1=1v-6 | | 4(8+m)= | | -8+x+6=2x+x | | A(w-3)+5=3(w-1) | | 6r-1+6=6r | | 8x^2-16x-80=1 | | -5-(15y-1)=2(17-16)-y | | -8.0a-8=0.2a | | 3x+4+4x+6x-11+5x-7=85 | | -6x-4=-52 | | 90=4y+10 | | 5x^2-16x-340=0 | | 8-w=8 | | h=81.688+2.392*50.1 | | 3(6+5y)= | | a^2-169=0 | | 10x+1=-9 | | 8senx-3=0 | | F(t)=-16t^2+45t+6 | | -8x-8+2x=-2x | | (180-x)+(90-x)=210 | | 3x^2-8x-340=0 | | (n-8)-(2n+2)= | | 15x-4=x-1 | | 3(-2m+5)=-4m+9-m |